2009
DOI: 10.1515/jpem.2009.22.5.409
|View full text |Cite
|
Sign up to set email alerts
|

School-based Exercise Improves Fitness, Body Composition, Insulin Sensitivity, and Markers of Inflammation in Non-Obese Children

Abstract: The school-based fitness oriented curriculum resulted in improved body composition and insulin sensitivity, increased CVF, and decreased inflammation in non-obese children. Combined with prior studies, these data demonstrate that school-based fitness curricula can benefit both obese and non-obese children. Partnerships with schools to promote fitness should be part of a public health approach to improving children's health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 30 publications
2
33
0
1
Order By: Relevance
“…Studies show that increased practice of physical exercise increases the plasma concentrations of adiponectin (anti-inflammatory agent that increases sensitivity to insulin action), and decreases levels of IL-6 and TNF-α 19 , with this protective effect being observed since early ages 20 . …”
Section: Discussionmentioning
confidence: 99%
“…Studies show that increased practice of physical exercise increases the plasma concentrations of adiponectin (anti-inflammatory agent that increases sensitivity to insulin action), and decreases levels of IL-6 and TNF-α 19 , with this protective effect being observed since early ages 20 . …”
Section: Discussionmentioning
confidence: 99%
“…Few other intervention studies report significant changes such as these after such limited exposure. The majority of these studies demonstrate changes as a result of interventions lasting in the region of a year for cardiovascular fitness 18 and psychosocial measures, 19 but sometimes up to 3 years for psychosocial variables. 20 Limitations of this study include the lack of rigorous monitoring data to support the evaluation, limited data collected from control schools, and the small number of learners tested at control schools.…”
Section: Discussionmentioning
confidence: 99%
“…However, intervention studies have shown increases in adiponectin levels with or without weight reduction and increasing physical fitness. 31,36,38,[161][162][163][164] The increase in adiponectin levels was mostly related to improvements in insulin resistance and other inflammatory factors in children.…”
Section: Adiponectinmentioning
confidence: 99%